2013
DOI: 10.4236/ojmi.2013.33014
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Review of Adolescent Tibial Tuberosity Fractures

Abstract: Adolescent tibial tuberosity injuries are infrequent fractures usually seen in physically active adolescent males. Powerful contraction of the knee extensors by sudden acceleration or deceleration of the quadriceps muscle can result in avulsion fractures of the tibial tuberosity apophysis. In late puberty, as the growth plate closes, it is transiently replaced by fibrocartilaginous elements. This transition causes a period of weakened tensile strength, which predisposes the tibial tuberosity to traction injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Common imaging modalities used to assess either the physiologic maturation or detect various pathologies of the tibial tuberosity include radiography, magnetic resonance imaging and ultrasound [6,10]. Although radiography is a valuable imaging tool for diagnosing traction injuries, such as avulsion fractures, it has some important limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Common imaging modalities used to assess either the physiologic maturation or detect various pathologies of the tibial tuberosity include radiography, magnetic resonance imaging and ultrasound [6,10]. Although radiography is a valuable imaging tool for diagnosing traction injuries, such as avulsion fractures, it has some important limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The resemblance of the tibial tuberosity to that of an inverted-U, seen in 100% of dry tibiae in the current study, may serve as the standard around which fracture patterns of avulsion injuries of the tuberosity may be accurately evaluated (Chitkara et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that proximal tibial avulsion fractures occur more frequently in adolescent males, who are both athletic and muscular [4]. Physiologic physiodesis occurs at a later age in males, which can place the tubercle at greater risk of injury [5]. This, combined with males being larger, heavier with stronger quadriceps, places greater strain through the tibial tubercle, which may predispose to avulsion type injury [4].…”
Section: Introductionmentioning
confidence: 99%